Break up or wrap? Therapeutic Possibilities for the Treatment of Alzheimer´s disease by altering the aggregation of beta-amyloid peptide - Fülöp Lívia (Neuropeptides and peptide analogs, 2009)
The occurrence of Alzheimer´s disease (AD) grows dramatically with the mean age of the human population. This devastating neurodegenerative disorder causes an increasing financial burden on the individuals and the society. Currently existing therapies can provide only symptomatic relief by slowing down the mental breakdown and improving cognitive and behavioral functions temporarily. AD is a so-called `protein misfolding disease´, as its course is strongly related to the production, aggregation, and consequent accumulation of a peptide named beta-amyloid (Aβ) in the brain. In this review, we summarize the results of the investigations that have aimed to alter the aggregation pathway of Aβ and present the most promising drug candidates possessing aggregation inhibitory activity, which could serve as efficient causative therapeutics in the future.